PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN YANG MENGINAP PADA HOTEL BUMI SENYIUR SAMARINDA - Edi Gusnaedi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
This study aims: (i) to test and analyze the effect of service quality variables consisting of reliability, responsiveness, assurance, empathy, and physical evidence simultaneously (ii) to test and analyze the effect of service quality variables consisting of reliability, responsiveness , guarantee, empathy and physical evidence partially (iii) to test and analyze the influence of service quality which consists of reliability, responsiveness, assurance, empathy and physical evidence that most influence on customer satisfaction staying at the Bumi Senyiur Hotel Samarinda. This study uses two variables namely the variable service quality and customer satisfaction. This type of research is quantitative, the population is 12,532 with a sample of 100. Data collection techniques: field research, observation, interviews, questionnaires, and library research. Then the analysis technique used is linear regression using the test: validity test, reliability test, classic assumption test, normality test, multicollinearity test, autocorrelation test, multiple linear analysis. The results obtained in this study are (i) service quality variables consisting of: reliability, responsiveness, assurance, empathy and physical evidence simultaneously affect the satisfaction of consumers who stay at the Hotel Bumi Senyiur Samarinda. (ii) service quality variables consisting of: reliability, guarantee and empathy partially have a significant effect on customer satisfaction staying at Bumi Senyiur Hotel Samarinda. (iii) guarantee variable which has the most significant effect on customer satisfaction staying at Bumi Senyiur Samarinda Hotel.